Self-regulated learning in the digital age: An EFL perspective - Kızıl, Aysel Şahin; Savran, Zehra (My University, 2016)
Research on the role of Information and Communication Technologies (ICT) in language learning has ascertained heretofore various potentials ranging from metacognitive domain to skill-based practices. One area in which the potentials of ICT tools requires further exploration is self-regulated language learning, an active, constructive process in which learners take the initiative in their learning experiences. This paper reports on a study which aims to examine English as a Foreign Language (EFL) learners’ use of ICT tools to self-regulate their language learning outside the formal instructional setting. A total of 777 university students attending an intensive English language preparatory program participated in the study. Analysis of the data collected through surveys showed that EFL learners were actively engaged in the use of ICT tools for self-regulated language learning, but there were variations both among the students and in aspects of regulating learning through the use of ICT tools.

Dil öğreniminde bilgi ve iletişim teknolojilerinin kullanımı konusunda yürütülen araştırmalar, şimdiye dek üst bilişsel alandan dil becerileri temelli uygulamalara kadar, teknolojik araçların birçok farklı potansiyelini ortaya koymuştur. Bilgi ve iletişim teknolojilerinin potansiyelinin daha fazla araştırılması gereken bir alan da, öğrencilerin kendi öğrenme süreçleriyle ilgili girişimde bulunduğu etkin ve yapıcı bir süreç olan öz-düzenleyici dil öğrenimi alanıdır. Bu çalışma, yabancı dil olarak İngilizce öğrenicilerinin okul dışında öz-düzenleyici dil öğrenimi faaliyetlerinde bilgi ve iletişim teknolojileri kullanımlarını incelemektedir. Çalışmaya, İngilizce hazırlık programına devam eden 777 üniversite öğrencisi katılmıştır. Anket yoluyla toplanan verilerin analizi İngilizce öğrenicilerinin öz-düzenleyici dil öğrenimi faaliyetlerinde aktif bir şekilde bilgi ve iletişim teknolojilerini kullandığını, ancak hem öğrenciler arasında hem de öğrenmenin düzenlenen yönleri açısından farklılıklar olduğunu göstermiştir.
Dijital çağda öz-düzenleyici öğrenme: Yabancı dil olarak İngilizce bağlamı
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Self-regulated learning; Information and communication technologies; ICT; English as a foreign language; EFL learners